The Availability of Basic Sanitation to the Incidence of Stunting in Toddlers in the Coastal Area of Tamangapa Village, Pangkep Regency - Ayu Puspitasari; Didit Fachri Rifai; Harpiana Rahman; Nurhikmawati Abdullah; Andi Batari Salsabilla; Nurfachanti Fattah; Nurhikmawati Nurhikmawati (Universitas Nahdlatul Ulama Surabaya, 2026)
The problem of malnutrition, including stunting, is greatly influenced by environmental sanitation and personal hygiene. This paper examines the influence of the availability of trash bins, Waste Water Drainage Channels (Saluran Pembuangan Air Limbah or SPAL), and toilets on the incidence of stunting in toddlers in the Coastal Area of Tamangapa Village. This paper was a quantitative descriptive study. This study was conducted in Tamangapa Village from September to November 2024. The population was mothers with toddlers in Tamangapa Village, Pangkep Regency. The sample consisted of 72 respondents. The data source used primary data obtained through questionnaires. The analysis test used regression analysis. The results showed that the availability of trash bins (p = 0.000), SPALs (p = 0.000), and toilets (p = 0.003) affected the incidence of stunting in toddlers. In conclusion, the availability of basic sanitation (including trash bins, wastewater disposal channels, and toilets) has a significant impact on the incidence of stunting in toddlers in the coastal area of Tamangapa Village, Pangkep Regency.